Serum Micronutrients in Helminth-infected Pregnant Women and Children: Suggestions for Differential Supplementation During Anti-helminthic Treatment - Ganiyu Olatunbosun Arinola (Ubiquity Press, 2016)
Background: The prevalence of helminth infection, which is known to affect nutritional status of the host, varies with age. The complex interplay between ages, nutrient requirements, and infection necessitated the need to recommend micronutrient supplementation during helminth infection among different age groups. Objective: The aim of this study was to determine the pattern of alteration in selected micronutrients in pregnant women and preschool- and school-aged children with helminth infection. Methods: We screened 245 pregnant women and 349 children for helminth infection. Of these, 17 (6.9%) pregnant women and 102 (29.2%) children (42 preschool- and 60 school-aged) had helminth infection. Only 'Ascaris lumbricoides' was found in pregnant women, whereas the children had 'A lumbricoides', hookworm, 'Fasciola hepatica', and 'Trichuris' trichiura infections. The helminth-infected (HI) pregnant women, preschool-aged children, and school-aged children were matched with helminth-negative (HN) pregnant women (n = 21), preschool-aged children (n = 42), and school-aged children (n = 50) who served as controls. Venous blood samples were obtained and analyzed for iron (Fe), zinc (Zn), selenium (Se), and vitamins A and C. Statistical analysis was done using Student’s 't' test, and 'P' < 0.05 was considered statistically significant. Findings: Serum levels of Fe, Zn, and Se were significantly lower in HI pregnant women than HN pregnant women. In preschool-aged children, serum levels of Fe, Zn, and vitamin A were significantly lower in the HI than in the HN group. Similarly, serum levels of Zn and vitamin A were significantly lower in HI school-aged children than in the HN group. However, serum levels of Se were significantly higher in HI children (both age groups) than in the corresponding HN group. Conclusion: Helminth infection alters different types of micronutrients in children and pregnant women. Results from the present study therefore suggest monitoring Fe, Zn, or vitamin A supplementation with an anti-helminthic regimen.